Data Loss Study in Zonal Systems and Servers in a Shopping Center Parking Lot - Santillán Carranza, Holger Jorge; Feijoo Roman, Carlos Manuel; Alcivar Sanchez , Anthony Santiago; Cárdenas Villacrés, David Humberto; Wong Wong, Peregrina Maria Amparo (INGENIO, 2025)
This study analyzes the packet loss in the radio link of PowerBeam 5AC Gen2 antennas connected to various Meypar equipment in the “red dot” area of the Guayaquil shopping center. The objective is to optimize communication and ensure a stable network environment for the equipment. A tester was used to measure the continuity of the cabling, and oxidation was observed in all eight strands. In addition, Wireshark software was used to analyze packet traffic on 14 devices, including 1 transmitter, 1 ticket validator, 6 perimeter cameras, 2 license plate cameras, 2 IP intercoms and 2 antennas. Four critical scenarios were identified: the license plate cameras (1600 packets), the transmitter (293 packets) and the ticket validator (280 packets), registering a total of 2173 packets lost in these devices. To solve this problem, an exhaustive analysis of the IT infrastructure was carried out, identifying critical failures and implementing backup solutions, data recovery and system security improvements, thus minimizing the risk of data loss and ensuring the operational continuity of the parking lot. Para abordar el problema, se llevó a cabo un análisis exhaustivo del sistema zonal, identificando fallos críticos en la infraestructura de TI. Se implementaron soluciones de respaldo y recuperación de datos, junto con mejoras en la seguridad del sistema, logrando así minimizar el riesgo de pérdida de datos y asegurando la continuidad operativa del parqueadero.